Sistem Informasi Persediaan Pada Zam Komputer Menggunakan PHP dan MYSQL - Saira Asmar; Indra kanedi; Venny Novita Sari (Pusat Riset dan Inovasi Nasional, 2024)
In this era, shops also really need a data management information system to simplify and expedite performance in storing large amounts of data, where the system that is still used is conventional where purchases still use notes, making it ineffective, with the existence of the